Development of Aquatic Biology E-Module Based on Potential of Lake Lebo Taliwang - Ari Ashari; Hamdani (Jurnal Penelitian Pendidikan IPA, 2025)
The need for using digital technology such as E-Modules in learning is becoming increasingly important. Learning integrated with local potential such as Lake Lebo in Taliwang, which is located in the area, can create a unique learning environment and learning experiences. Therefore, development research needs to be conducted by utilizing the ease of access to technology in the form of E-Modules, with the main goal of developing a feasible and valid E-Module for Aquatic Biology, leveraging local potential such as Lake Lebo. The method in this research is development research referring to the 4D development model with 4 stages: Define, Design, Develop, and Disseminate. In this study, the stages to be carried out will only reach the Develop stage. The result indicates that the developed E-Module for Aquatic Biology is highly suitable for implementation in the learning process. Which is the score of 92 from Validator 1 falls into the very feasible category, while a score of 85 from Validator 2 falls into the feasible category. The readability test aspect of the developed E-Module on Aquatic Biology Based on the Potential of Lake Lebo Taliwang also got average 86, which falls into the very feasible criteria. This result indicates that the developed E-Module for Aquatic Biology is highly suitable for implementation in the learning process.